In Situ Techniques to Study the Effects of Anode or Cathode Gas‐Exchange Cycles on the Deterioration of Pt/C Cathode Catalysts in PEFCs. Issue 10 (20th May 2015) - Samjeské, Gabor; Higashi, Kotaro; Takao, Shinobu; Nagamatsu, Shin‐ichi; Nagasawa, Kensaku; Sekizawa, Oki; Kaneko, Takuma; Uruga, Tomoya; Iwasawa, Yasuhiro
Abstract Repeated, quick anode gas‐exchange (AGEX) or cathode gas‐exchange (CGEX) cycles were applied to polymer electrolyte fuel cell (PEFC) membrane electrode assemblies (MEAs) with Pt/C cathode catalysts to simulate start‐up/shut‐down conditions and to examine a possible countermeasure for their effects on MEA cathode catalyst degradation. The peak height of the white line during in situ time‐resolved X‐ray absorption near‐edge structure (XANES) spectra at the Pt LIII‐edge decreased with an increasing number of AGEX cycles and only in the top region of the MEA cathode layer (close to the gas inlet of the fuel cell), not in the whole MEA area. End‐of‐life analysis after AGEX by using SEM and TEM revealed isolated Pt nanoparticles in micro‐cracks and voids produced in the top region of the MEA cathode layer. The nanoparticle sizes remained almost unchanged for top, middle, and bottom regions of the MEA cathode layer. In the case of CGEX, a small increase in the Pt nanoparticle sizes in the top and bottom positions of the MEA cathode layer was observed. These findings support the role of carbon corrosion, leaving isolated, electrochemically inactive Pt nanoparticles as a consequence of the harsh reaction conditions caused by the reverse current decay mechanism during the start‐up/shut‐down phase, as in the case of AGEX cycles, to be the main cause for the cathode catalyst deterioration close to the anode gas inlet. On the other hand, the hydrogen gas feed to both the anode and cathode during start‐up and shut‐down processes seems to effectively suppress carbon corrosion and prevents a decrease in the performance.